2014
DOI: 10.1007/s11255-014-0798-7
|View full text |Cite
|
Sign up to set email alerts
|

The management of urethral stricture after kidney transplantation

Abstract: Urethral strictures after kidney transplantation are rare, and they can be safely and effectively treated by urethral dilation, internal urethrotomy or urethra reconstruction. Avoiding iatrogenic injury and shortening catheterization time may help reduce the risk of this complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…The amount of time for the urethral stricture to develop was 2e7 months (average, 4.4 mo). There was an increase in postoperative Qmax values [7]. As mentioned in this study, urethral stricture is one of the complications following renal transplantation.…”
Section: Discussionsupporting
confidence: 61%
“…The amount of time for the urethral stricture to develop was 2e7 months (average, 4.4 mo). There was an increase in postoperative Qmax values [7]. As mentioned in this study, urethral stricture is one of the complications following renal transplantation.…”
Section: Discussionsupporting
confidence: 61%
“…Urethral strictures may be associated with iatrogenic urethral injury, prolonged catheterization time and urinary tract infection. Therapeutic options include urethral dilation, endoscopic urethrotomy or urethra reconstruction [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…This differs from Xie et al, which reported a mean time from transplant to urethral stricture of 4.4 months (range 2-7 months), and Gökçe et al, which reported a time from transplant to urethrography and cystoscopy of 17.5 months (range 1-85 months). 9,11 At our centre, all RTRs had their ureteric stent removed via office cystoscopy 6-8 weeks after transplant surgery. Stent removal is typically the first in-person follow-up appointment most transplant patients have with transplant urology, which is likely when concerns regarding stricture-related symptoms would be first discussed, or else found incidentally on cystoscopy.…”
Section: © 2023 Canadian Urological Associationmentioning
confidence: 99%
“…10 Patients with postoperative strictures generally present with dysuria, frequency, or hydronephrosis. 11 To the best of our knowledge, no research has been carried out to described postoperative urethral strictures in RTRs using a Canadian population. The objective of this study was to characterize urethral stricture disease in male RTRs from a single METHODS A single-center retrospective chart review was conducted on adult male RTRs (aged 19 years and older) who received a renal transplant at Vancouver General Hospital (VGH) between October 1, 2009 and October 1, 2019, and who developed a postoperative urethral stricture.…”
Section: Introductionmentioning
confidence: 99%